Diclofenac, ibuprofen, and paracetamol biodegradation: overconsumed non-steroidal anti-inflammatories drugs at COVID-19 pandemic - Ferreira, Beatriz L.; Ferreira, Dionisia P.; Borges, Swanny F.; Ferreira, Adriana M.; Holanda, Fabricio H.; Ucella-Filho, João G. M.; Cruz, Rodrigo Alves S.; Birolli, Willian G.; Luque, Rafael; Ferreira, Irlon M. (Frontiers in Microbiology, 2023)
The consumption of non-steroidal anti-inflammatory drugs (NSAIDs) have increased significantly last year (2022), especially for patients in COVID-19 treatment. NSAIDs such as diclofenac, ibuprofen, and paracetamol are often available without restrictions, being employed without medical supervision for basic symptoms of inflammatory processes. Furthermore, these compounds are increasingly present in nature constituting complex mixtures discarded at domestic and hospital sewage/wastewater. Therefore, this review emphasizes the biodegradation of diclofenac, ibuprofen, and paracetamol by pure cultures or consortia of fungi at in vitro, in situ and ex situ processes. Considering the influence of different factors (inoculum dose, pH, temperature, co-factors, reaction time, and microbial isolation medium) relevant for the identification of highly efficient alternatives for pharmaceuticals decontamination, since biologically active micropollutants became a worldwide issue that should be carefully addressed. In addition, we present a quantitative bibliometric survey, which reinforces that the consumption of these drugs and consequently their impact on the environment goes beyond the epidemiological control of COVID-19.